PERKULIAHAN DARING DAN TATAP MUKA: ANTARA CITA DAN REALITA - Baso Iping; Haeran Haeran (Jurnal Inovasi Penelitian, 2021)
This research explains about online lecturing and face to face. The purpose of this research is to know expectation and reality which is reached from online lecturing system. This research is qualitative research. The source of data used is primary and secondary data. Data collection procedure is library and field research. Data analyzed by descriptive qualitative. The result of research shows that online lecturing has given expectation and many advantages from system of lecturing unattached by time and many other advantages. The great expectation to increase the educational quality in Indonesia to increase Indonesian human resources. Otherwise, from the expectation of online lecturing there are so many problems, such as college student difficult to understand concept, lack of understanding the materiel, limited quota, lack of interaction between lectures ad college students, and lack of controlling in studying.